KEBERTAHANAN KOSAKATA KELADANGAN BAHASA KULISUSU - Rikal Jufri; La Yani Konisi; Sulfiah (Jurnal Bastra (Bahasa dan Sastra), 2025)
The problem of this research is "how is the level of sustainability of the Kulisusu language field vocabulary in Waculaea Village, Kulisusu District, North Buton Regency". The purpose of this study is to describe the level of sustainability of the Kulisusu language field vocabulary in Waculaea Village, Kulisusu District, North Buton Regency. The type of research used in this paper is field research using qualitative methods supported by quantitative analysis in describing the level of sustainability of its vocabulary. The data collection technique uses a questionnaire. Based on the research results, it shows that the vocabulary that is still understood and known by all respondents reaches 2,141 vocabularies divided by the number of vocabularies in all questionnaires of 2500 vocabularies multiplied by 100%, so that the percentage of survival of farming vocabulary in Waculaea Village, Kulisusu District, North Buton Regency is 85.64%, while the number of vocabularies that are not understood is 359 vocabularies divided by the number of vocabularies in all questionnaires of 2500 vocabularies multiplied by 100%, with a percentage of 14.36%. It can be concluded that the Survival of Farming Vocabulary in Waculaea Village, Kulisusu District, North Buton Regency is still